Oxidative/Antioxidative Status in Obese and Sport Trained Children: A Comparative Study. (31st March 2015) - Matusik, Pawel; Prokopowicz, Zofia; Norek, Berenika; Olszanecka-Glinianowicz, Magdalena; Chudek, Jerzy; Malecka-Tendera, Ewa
Abstract : The aim of the study was to compare oxidative/antioxidative status in obese and sport trained children and to correlate obtained redox markers with anthropometrical measurements, body composition parameters, and adipokines levels. 78 (44 males) obese (SG) and 80 (40 males) normal weight sport trained (CG) children matched for age and Tanner stage were recruited for the study. Body composition parameters and basal metabolic rate (BMR) were assessed by bioelectrical impedance analysis (BIA). Oxidative/antioxidative status was evaluated in plasma by total oxidative status (PerOX), oxidized-LDL cholesterol (oxLDL), total antioxidative capacity (ImAnOx), and glutathione peroxidase activity (GPx). Leptin and adiponectin levels and adiponectin/leptin ratio (A/L) were also investigated. OxLDL was higher in SG versus CG ( P  < 0.05), but ImAnOx and GPx were reduced in SG versus CG ( P  < 0.01). Redox markers correlated significantly with BMI Z -score, WHR, WHtR, body composition parameters, leptin (in boys only), and A/L ratio (in boys only) in SG and in a whole studied population. PerOX significantly correlated with BMR in the CG. Antioxidative/oxidative status in obese children is significantly impaired and related adipose tissue excess and its hormonal activity. Oxidative status assessed by PerOx is also high in sport trained children but antioxidative defense is significantly more efficient with no overproduction of oxidized LDL.